STRATEGI MEDIA RELATIONS BADAN NARKOTIKA NASIONAL KABUPATEN BANDUNG BARAT DALAM UPAYA MEMBANGUN CITRA LEMBAGA - Thoriq Ibrahim; Yustikasari Yustikasari; Evi Novianti (Jurnal Inovasi Penelitian, 2022)
In achieving Kabupaten Bandung Barat’s Indonesia National Narcotics Board organization goal in preventing drug abuse, organization credibility which is reflected by its image in the eye of its public needs to be attained. One of the ways of achieving so is by maximizing positive publication by executing media relations strategies that consist of steps to create good cooperation with the media. Across the year 2019, Kabupaten Bandung Barat’s Indonesia National Narcotics Board had successfully publicized more than 60 news article on online media platforms ranging from local to provincial scope. The goal of this research is to describe Kabupaten Bandung Barat’s Indonesia National Narcotics Board’s Media Relations Strategy. Using descriptive qualitative research method by utilizing observation, interview, and documentation technique which based on Media Relations Strategy concept. Research indicated that it’ successful publication linked to the media relations strategy that consist of serving the media by providing information according to what the media suppose important, providing information that is relevant and promptly, arranging publication material which is in line with good journalistic rule to the media, cooperative in providing information to the media, openess in giving explanation about a certain issue when questioned by the media, building a kinship relations with the media.Abstract is written concisely and factually, includes the background of research, the purpose of research, the method of research, the result of research, conclusion, and reccomendation.